2021
DOI: 10.1088/1755-1315/735/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Fertilizer on Growth and Calyx Yield of Roselle (Hibiscus sabdariffa L.) Grown under Field Conditions

Abstract: Assessments of growth, calyx yield and nutritional composition of roselle can help farmers in Iraq to determine which cultivars are the best for commercialization. The field experiment has been done on two roselle cultivars (red and white) during summer of 2019 in a private farm that belongs to a farmer in Al-Saniyah county, Al-Diwaniyah, Al-Qadisiyah province, Iraq, to investigate the impact of applying various rates of N fertilizer (0, 30, 60, 90, and 120 kg N/ha) on some agronomic traits and calyx yield. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Additionally, nitrogen is also enhanced root growth by increasing root length and root weight, which leaded to increase the water and nutrient uptake in the chamomile plants [8,29]. In accordance with current study, the influence of nitrogen fertilizer on plant growth improvement has been observed in several medicinal species such as [22] and [14].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Additionally, nitrogen is also enhanced root growth by increasing root length and root weight, which leaded to increase the water and nutrient uptake in the chamomile plants [8,29]. In accordance with current study, the influence of nitrogen fertilizer on plant growth improvement has been observed in several medicinal species such as [22] and [14].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, this field study found that nitrogen deficiency affects the development of medicinal and aromatic plants and the production of essential oils [21]. It is proved by studies, the nitrogen source and application rates are essential factors that could manipulate the growth and production of essential oils in medicinal and aromatic herbs [12,14,22]. [23], the availability of studies that reviewed the influence of nitrogen application on chamomile growth and essential oil quality was limited, but we could summarize the main results.…”
Section: Introductionmentioning
confidence: 99%